IMPLEMENTASI PENGENDALI LAYAR PROYEKTOR DENGAN ANDROID - dwi, Yuningrat putri (CV. Hawari, 2022)
The use of Liquid Crystal Display (LCD) in daily activities is often hampered because you still have to use a laptop or computer for features to deliver presentations, therefore this research designed an LCD projector control system using a smartphone, where the LCD projector can be controlled using a smartphone, either it turns on, turns off, or whoever the source of information or video that wants to be displayed on the LCD projector can only use a smartphone. This system uses a Raspberry Pi as the link between the LCD projector and the smartphone, the screen display from the smartphone will be sent to the Raspberry Pi via a wifi network, which will then be displayed on the LCD projector. As well as in tests that try to measure the strength of the WIFI signal against the distance obtained if this system can run properly with a maximum distance between the smartphone and raspberry pi 18 meters. And the ideal distance is 10 meters. As well as for the Quality of Service (QoS) test, the average delay value resulting from measurements from various points is 359ms. And the average throughput value is 169.3KBps.